The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1364/josab.29.002665
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the refractive index change at the surface and inside phosphate glass upon femtosecond laser irradiation

Abstract: A study of the surface modification induced by single femtosecond laser pulses in phosphate glass has revealed surface swelling at fluences just below the ablation threshold. This behavior is different from that observed in other dielectric materials. Optical micrographs obtained with monochromatic light show a pattern of Newton rings within the swollen region whose number scales inversely with the illumination wavelength, acting as a micro Fabry-Perot etalon. The swollen surface layer has lower refractive ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The nature of such rings was initially attributed to shockwaves in the surface due to hydrodynamic effects in the melted material [12]. Recent studies [14] have demonstrated that the melted material acts as a micro Fabry-Perot etalon formed between the laser-produced top layer of lower refractive index than the underneath bulk material, separated by a sharp optical interface. A study of the number, thickness and displacement of the dynamically moving Newton fringes allows the generation of different quantitative parameters as the thickness of the melted volume, the dynamic of the refractive index of the melted pool and the estimation of the electron plasma density [15].…”
Section: Resultsmentioning
confidence: 99%
“…The nature of such rings was initially attributed to shockwaves in the surface due to hydrodynamic effects in the melted material [12]. Recent studies [14] have demonstrated that the melted material acts as a micro Fabry-Perot etalon formed between the laser-produced top layer of lower refractive index than the underneath bulk material, separated by a sharp optical interface. A study of the number, thickness and displacement of the dynamically moving Newton fringes allows the generation of different quantitative parameters as the thickness of the melted volume, the dynamic of the refractive index of the melted pool and the estimation of the electron plasma density [15].…”
Section: Resultsmentioning
confidence: 99%
“…This fact indicates that the ratio between the number of fringes and wavelength is approximately constant, verifying the interferometric origin for the fringe pattern, corresponding to Newton fringes caused by a semitransparent, superficially modified surface layer. We previously observed and studied this kind of interference effect for irradiations in phosphate glass, using 100 fs transformlimited pulses [25]. In the current investigation, we modeled the ring pattern observation by analogy with a micro-FabryPerot system, a laser-induced thin surface layer with different optical properties as sketched in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7 Second, it features surface swelling at fluences just below the ablation threshold (F th ¼ 3.8 J/cm 2 ), offering an ideal fluence window for studying the formation and evolution of the HAL without being shielded by ablation effects. 7,12 Figure 2 shows the effect induced by a single pulse at a fluence of 3.7 J/cm 2 , slightly below the ablation threshold. The optical microscopy (OM) image shows the appearance of Newton rings.…”
Section: -9mentioning
confidence: 99%
“…Using a simple Drude model, a maximum carrier density of n e ¼ 1.1 Â 10 22 cm À3 can be estimated. 12 At t ¼ 20 ps, the reflectivity has decreased below that of the non-excited material (by a factor $0.5). While this behavior might be interpreted as a sign of ablation, it should be kept in mind that the fluence employed is below the ablation threshold (see the AFM image in Fig.…”
Section: -9mentioning
confidence: 99%
See 1 more Smart Citation